Remittances Potential and its Contribution to Economic Growth of Pakistan - Khan, Naveed Khalid (Journal of Pakistan Administration, 2025)
The global flow of remittances in the last year was ever highest in the history, surpassing the foreign direct investment and foreign aid. This important transfer of money has positive economic implications for the recipient countries both at micro and macro level. The trends in the flow of remittances indicate that this will continue in future as well. Pakistan is among the top ten highest recipients of remittances. This important source of income for the families of the migrants is providing them necessary lifeline. Remittances are also important source of external finance and used for bridging the trade deficit. Unfortunately, the remittances flow in Pakistan have some challenges from the informal channels as well as high dependency on semi or unskilled workforce in the GCC countries. The study of the example of Philippines have indicated that the remittances can be increased by adopting a focused and coordinated mechanism. The prime responsibility of managing the overseas workforce should be given to one organization. The workforce demand analysis in the host countries should be done in a scientific manner and the future requirements and projections be prepared. The workforce specialized training programs should be designed in view of the demand of the host countries. The skills imparting and focused modules be made permanent features in technical education system so that the required workforce is available. There should be centralized and coordinated mechanism for recruitment and training and multiplicity of administrative structures should be done away with and be replaced by a single professional, proactive, forward looking and research focused organization. Finally, some innovative solutions for transfer of money by the migrant workers be designed so that the informal channels can be reduced and more flow be ensured in formal banking system.